lean2/library/data/list/basic.lean

392 lines
13 KiB
Text
Raw Normal View History

/-
Copyright (c) 2014 Parikshit Khanna. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Module: data.list.basic
Authors: Parikshit Khanna, Jeremy Avigad, Leonardo de Moura
Basic properties of lists.
-/
2014-12-01 04:34:12 +00:00
import logic tools.helper_tactics data.nat.basic
open eq.ops helper_tactics nat prod function
inductive list (T : Type) : Type :=
| nil {} : list T
| cons : T → list T → list T
namespace list
notation h :: t := cons h t
notation `[` l:(foldr `,` (h t, cons h t) nil) `]` := l
variable {T : Type}
/- append -/
definition append : list T → list T → list T
| append nil l := l
| append (h :: s) t := h :: (append s t)
notation l₁ ++ l₂ := append l₁ l₂
theorem append_nil_left (t : list T) : nil ++ t = t
theorem append_cons (x : T) (s t : list T) : (x::s) ++ t = x::(s ++ t)
theorem append_nil_right : ∀ (t : list T), t ++ nil = t
| append_nil_right nil := rfl
| append_nil_right (a :: l) := calc
(a :: l) ++ nil = a :: (l ++ nil) : rfl
... = a :: l : append_nil_right l
theorem append.assoc : ∀ (s t u : list T), s ++ t ++ u = s ++ (t ++ u)
| append.assoc nil t u := rfl
| append.assoc (a :: l) t u :=
show a :: (l ++ t ++ u) = (a :: l) ++ (t ++ u),
by rewrite (append.assoc l t u)
/- length -/
definition length : list T → nat
| length nil := 0
| length (a :: l) := length l + 1
theorem length_nil : length (@nil T) = 0
theorem length_cons (x : T) (t : list T) : length (x::t) = length t + 1
theorem length_append : ∀ (s t : list T), length (s ++ t) = length s + length t
| length_append nil t := calc
length (nil ++ t) = length t : rfl
... = length nil + length t : zero_add
| length_append (a :: s) t := calc
length (a :: s ++ t) = length (s ++ t) + 1 : rfl
... = length s + length t + 1 : length_append
... = (length s + 1) + length t : add.succ_left
... = length (a :: s) + length t : rfl
-- add_rewrite length_nil length_cons
/- concat -/
definition concat : Π (x : T), list T → list T
| concat a nil := [a]
| concat a (b :: l) := b :: concat a l
theorem concat_nil (x : T) : concat x nil = [x]
theorem concat_cons (x y : T) (l : list T) : concat x (y::l) = y::(concat x l)
theorem concat_eq_append (a : T) : ∀ (l : list T), concat a l = l ++ [a]
| concat_eq_append nil := rfl
| concat_eq_append (b :: l) :=
show b :: (concat a l) = (b :: l) ++ (a :: nil),
by rewrite concat_eq_append
-- add_rewrite append_nil append_cons
/- reverse -/
definition reverse : list T → list T
| reverse nil := nil
| reverse (a :: l) := concat a (reverse l)
theorem reverse_nil : reverse (@nil T) = nil
theorem reverse_cons (x : T) (l : list T) : reverse (x::l) = concat x (reverse l)
theorem reverse_singleton (x : T) : reverse [x] = [x]
theorem reverse_append : ∀ (s t : list T), reverse (s ++ t) = (reverse t) ++ (reverse s)
| reverse_append nil t2 := calc
reverse (nil ++ t2) = reverse t2 : rfl
... = (reverse t2) ++ nil : append_nil_right
... = (reverse t2) ++ (reverse nil) : {reverse_nil⁻¹}
| reverse_append (a2 :: s2) t2 := calc
reverse ((a2 :: s2) ++ t2) = concat a2 (reverse (s2 ++ t2)) : rfl
... = concat a2 (reverse t2 ++ reverse s2) : reverse_append
... = (reverse t2 ++ reverse s2) ++ [a2] : concat_eq_append
... = reverse t2 ++ (reverse s2 ++ [a2]) : append.assoc
... = reverse t2 ++ concat a2 (reverse s2) : concat_eq_append
... = reverse t2 ++ reverse (a2 :: s2) : rfl
theorem reverse_reverse : ∀ (l : list T), reverse (reverse l) = l
| reverse_reverse nil := rfl
| reverse_reverse (a :: l) := calc
reverse (reverse (a :: l)) = reverse (concat a (reverse l)) : rfl
... = reverse (reverse l ++ [a]) : concat_eq_append
... = reverse [a] ++ reverse (reverse l) : reverse_append
... = reverse [a] ++ l : reverse_reverse
... = a :: l : rfl
theorem concat_eq_reverse_cons (x : T) (l : list T) : concat x l = reverse (x :: reverse l) :=
calc
concat x l = concat x (reverse (reverse l)) : reverse_reverse
... = reverse (x :: reverse l) : rfl
/- head and tail -/
definition head [h : inhabited T] : list T → T
| head nil := arbitrary T
| head (a :: l) := a
theorem head_cons [h : inhabited T] (a : T) (l : list T) : head (a::l) = a
theorem head_concat [h : inhabited T] (t : list T) : ∀ {s : list T}, s ≠ nil → head (s ++ t) = head s
| @head_concat nil H := absurd rfl H
| @head_concat (a :: s) H :=
show head (a :: (s ++ t)) = head (a :: s),
by rewrite head_cons
definition tail : list T → list T
| tail nil := nil
| tail (a :: l) := l
theorem tail_nil : tail (@nil T) = nil
theorem tail_cons (a : T) (l : list T) : tail (a::l) = l
theorem cons_head_tail [h : inhabited T] {l : list T} : l ≠ nil → (head l)::(tail l) = l :=
list.cases_on l
(assume H : nil ≠ nil, absurd rfl H)
(take x l, assume H : x::l ≠ nil, rfl)
/- list membership -/
definition mem : T → list T → Prop
| mem a nil := false
| mem a (b :: l) := a = b mem a l
notation e ∈ s := mem e s
theorem mem_nil (x : T) : x ∈ nil ↔ false :=
iff.rfl
theorem mem_cons (x y : T) (l : list T) : x ∈ y::l ↔ (x = y x ∈ l) :=
iff.rfl
theorem mem_concat_imp_or {x : T} {s t : list T} : x ∈ s ++ t → x ∈ s x ∈ t :=
list.induction_on s or.inr
(take y s,
assume IH : x ∈ s ++ t → x ∈ s x ∈ t,
assume H1 : x ∈ y::s ++ t,
have H2 : x = y x ∈ s ++ t, from H1,
have H3 : x = y x ∈ s x ∈ t, from or_of_or_of_imp_right H2 IH,
iff.elim_right or.assoc H3)
theorem mem_or_imp_concat {x : T} {s t : list T} : x ∈ s x ∈ t → x ∈ s ++ t :=
list.induction_on s
(take H, or.elim H false.elim (assume H, H))
(take y s,
assume IH : x ∈ s x ∈ t → x ∈ s ++ t,
assume H : x ∈ y::s x ∈ t,
or.elim H
(assume H1,
or.elim H1
(take H2 : x = y, or.inl H2)
(take H2 : x ∈ s, or.inr (IH (or.inl H2))))
(assume H1 : x ∈ t, or.inr (IH (or.inr H1))))
theorem mem_concat (x : T) (s t : list T) : x ∈ s ++ t ↔ x ∈ s x ∈ t :=
iff.intro mem_concat_imp_or mem_or_imp_concat
local attribute mem [reducible]
local attribute append [reducible]
theorem mem_split {x : T} {l : list T} : x ∈ l → ∃s t : list T, l = s ++ (x::t) :=
list.induction_on l
(take H : x ∈ nil, false.elim (iff.elim_left !mem_nil H))
(take y l,
assume IH : x ∈ l → ∃s t : list T, l = s ++ (x::t),
assume H : x ∈ y::l,
or.elim H
(assume H1 : x = y,
exists.intro nil (!exists.intro (H1 ▸ rfl)))
(assume H1 : x ∈ l,
obtain s (H2 : ∃t : list T, l = s ++ (x::t)), from IH H1,
obtain t (H3 : l = s ++ (x::t)), from H2,
have H4 : y :: l = (y::s) ++ (x::t),
from H3 ▸ rfl,
!exists.intro (!exists.intro H4)))
definition decidable_mem [instance] [H : decidable_eq T] (x : T) (l : list T) : decidable (x ∈ l) :=
list.rec_on l
(decidable.inr (not_of_iff_false !mem_nil))
(take (h : T) (l : list T) (iH : decidable (x ∈ l)),
show decidable (x ∈ h::l), from
decidable.rec_on iH
(assume Hp : x ∈ l,
decidable.rec_on (H x h)
(assume Heq : x = h,
decidable.inl (or.inl Heq))
(assume Hne : x ≠ h,
decidable.inl (or.inr Hp)))
(assume Hn : ¬x ∈ l,
decidable.rec_on (H x h)
(assume Heq : x = h,
decidable.inl (or.inl Heq))
(assume Hne : x ≠ h,
have H1 : ¬(x = h x ∈ l), from
assume H2 : x = h x ∈ l, or.elim H2
(assume Heq, absurd Heq Hne)
(assume Hp, absurd Hp Hn),
have H2 : ¬x ∈ h::l, from
iff.elim_right (not_iff_not_of_iff !mem_cons) H1,
decidable.inr H2)))
/- find -/
section
variable [H : decidable_eq T]
include H
definition find : T → list T → nat
| find a nil := 0
| find a (b :: l) := if a = b then 0 else succ (find a l)
theorem find_nil (x : T) : find x nil = 0
theorem find_cons (x y : T) (l : list T) : find x (y::l) = if x = y then 0 else succ (find x l)
theorem find.not_mem {l : list T} {x : T} : ¬x ∈ l → find x l = length l :=
list.rec_on l
(assume P₁ : ¬x ∈ nil, _)
(take y l,
assume iH : ¬x ∈ l → find x l = length l,
assume P₁ : ¬x ∈ y::l,
have P₂ : ¬(x = y x ∈ l), from iff.elim_right (not_iff_not_of_iff !mem_cons) P₁,
have P₃ : ¬x = y ∧ ¬x ∈ l, from (iff.elim_left not_or_iff_not_and_not P₂),
calc
find x (y::l) = if x = y then 0 else succ (find x l) : !find_cons
... = succ (find x l) : if_neg (and.elim_left P₃)
... = succ (length l) : {iH (and.elim_right P₃)}
... = length (y::l) : !length_cons⁻¹)
end
/- nth element -/
definition nth [h : inhabited T] : list T → nat → T
| nth nil n := arbitrary T
| nth (a :: l) 0 := a
| nth (a :: l) (n+1) := nth l n
theorem nth_zero [h : inhabited T] (a : T) (l : list T) : nth (a :: l) 0 = a
theorem nth_succ [h : inhabited T] (a : T) (l : list T) (n : nat) : nth (a::l) (n+1) = nth l n
open decidable
definition decidable_eq {A : Type} [H : decidable_eq A] : ∀ l₁ l₂ : list A, decidable (l₁ = l₂)
| decidable_eq nil nil := inl rfl
| decidable_eq nil (b::l₂) := inr (λ H, list.no_confusion H)
| decidable_eq (a::l₁) nil := inr (λ H, list.no_confusion H)
| decidable_eq (a::l₁) (b::l₂) :=
match H a b with
| inl Hab :=
match decidable_eq l₁ l₂ with
| inl He := inl (eq.rec_on Hab (eq.rec_on He rfl))
| inr Hn := inr (λ H, list.no_confusion H (λ Hab Ht, absurd Ht Hn))
end
| inr Hnab := inr (λ H, list.no_confusion H (λ Hab Ht, absurd Hab Hnab))
end
section combinators
variables {A B C : Type}
definition map (f : A → B) : list A → list B
| map nil := nil
| map (a :: l) := f a :: map l
theorem map_nil (f : A → B) : map f nil = nil
theorem map_cons (f : A → B) (a : A) (l : list A) : map f (a :: l) = f a :: map f l
theorem map_map (g : B → C) (f : A → B) : ∀ l : list A, map g (map f l) = map (g ∘ f) l
| map_map nil := rfl
| map_map (a :: l) :=
show (g ∘ f) a :: map g (map f l) = map (g ∘ f) (a :: l),
by rewrite (map_map l)
theorem len_map (f : A → B) : ∀ l : list A, length (map f l) = length l
| len_map nil := rfl
| len_map (a :: l) :=
show length (map f l) + 1 = length l + 1,
by rewrite (len_map l)
definition foldl (f : A → B → A) : A → list B → A
| foldl a nil := a
| foldl a (b :: l) := foldl (f a b) l
definition foldr (f : A → B → B) : B → list A → B
| foldr b nil := b
| foldr b (a :: l) := f a (foldr b l)
definition all (p : A → Prop) : list A → Prop
| all nil := true
| all (a :: l) := p a ∧ all l
definition any (p : A → Prop) : list A → Prop
| any nil := false
| any (a :: l) := p a any l
definition decidable_all (p : A → Prop) [H : decidable_pred p] : ∀ l, decidable (all p l)
| decidable_all nil := decidable_true
| decidable_all (a :: l) :=
match H a with
| inl Hp₁ :=
match decidable_all l with
| inl Hp₂ := inl (and.intro Hp₁ Hp₂)
| inr Hn₂ := inr (not_and_of_not_right (p a) Hn₂)
end
| inr Hn := inr (not_and_of_not_left (all p l) Hn)
end
definition decidable_any (p : A → Prop) [H : decidable_pred p] : ∀ l, decidable (any p l)
| decidable_any nil := decidable_false
| decidable_any (a :: l) :=
match H a with
| inl Hp := inl (or.inl Hp)
| inr Hn₁ :=
match decidable_any l with
| inl Hp₂ := inl (or.inr Hp₂)
| inr Hn₂ := inr (not_or Hn₁ Hn₂)
end
end
definition zip : list A → list B → list (A × B)
| zip nil _ := nil
| zip _ nil := nil
| zip (a :: la) (b :: lb) := (a, b) :: zip la lb
definition unzip : list (A × B) → list A × list B
| unzip nil := (nil, nil)
| unzip ((a, b) :: l) :=
match unzip l with
| (la, lb) := (a :: la, b :: lb)
end
theorem unzip_nil : unzip (@nil (A × B)) = (nil, nil)
theorem unzip_cons (a : A) (b : B) (l : list (A × B)) :
unzip ((a, b) :: l) = match unzip l with (la, lb) := (a :: la, b :: lb) end
theorem zip_unzip : ∀ (l : list (A × B)), zip (pr₁ (unzip l)) (pr₂ (unzip l)) = l
| zip_unzip nil := rfl
| zip_unzip ((a, b) :: l) :=
begin
rewrite unzip_cons,
have r : zip (pr₁ (unzip l)) (pr₂ (unzip l)) = l, from zip_unzip l,
revert r,
apply (prod.cases_on (unzip l)),
intros (la, lb, r),
rewrite -r
end
end combinators
end list
attribute list.decidable_eq [instance]
attribute list.decidable_mem [instance]
attribute list.decidable_any [instance]
attribute list.decidable_all [instance]